2018
DOI: 10.17323/2411-7390-2018-4-1-79-91
|View full text |Cite
|
Sign up to set email alerts
|

There is no Alternative! Student Perceptions of Learning in a Second Language in Lebanon

Abstract: Since 1997, children in Lebanese state schools are taught most of the curriculum in English or French. The children’s first language, Arabic, may be used even less in private schools, which educate 70% of children. In many countries, mother tongue education is seen as a right but in Lebanon it is taken for granted that children are taught in English or French. Written opinions were collected from seventy-five university students who were asked about the language in education policy. The results of a thematic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 50 publications
(39 reference statements)
1
12
0
Order By: Relevance
“…They viewed English as a necessary medium of instruction at all levels of education placing English as the best means for studying science, technology, business and the media. They also viewed English as important for their future education or careers abroad placing English as the conduit to emigration (Orr and Annous, 2018).…”
Section: Students' Perceptions Of the Place English 101 Holds At The mentioning
confidence: 99%
“…They viewed English as a necessary medium of instruction at all levels of education placing English as the best means for studying science, technology, business and the media. They also viewed English as important for their future education or careers abroad placing English as the conduit to emigration (Orr and Annous, 2018).…”
Section: Students' Perceptions Of the Place English 101 Holds At The mentioning
confidence: 99%
“…However, some young Syrian refugees are trying to study English, (Casalone and Puig 2015;Riller 2009), which could help them immigrate to a third, safer country with better education opportunities and more respect for human rights (UNHCR 2017b). Moreover, English literacy increases their chances of enrolling and succeeding in Lebanese schools where science and math classes are taught in English or French (Orr and Annous 2018). Young Syrian refugees who are studying English while in Lebanon are in a similar situation as other refugees in transition to a third country.…”
Section: Transition Phase: Syrian Refugees In Lebanonmentioning
confidence: 99%
“…Spolsky (1978) had proposed a theory and model for bilingual education but at the same time highlighted its complexity and its dependency on certain factors and situations. However, political, economic and religious issues challenged colonialism and its implementation of English or French as a medium of instruction to the ousting of national languages as a kind of imperialism and power through indirect means which was met with disfavor in many countries worldwide (Orr & Annous, 2018;Zakharia, 2009). Nevertheless, putting the non-linguistic factors aside, the world, and especially in Lebanon, has become even more bilingual and multilingual as people and students travel, and emigrate to seek better opportunities.…”
Section: Bilingualismmentioning
confidence: 99%
“…There are even fewer at the university level. Orr and Annous (2018) indicated that students favored learning in English and French and not the national language Arabic. Arabic is not viewed by students as prestigious as English and French are and which are viewed as passports to continue their higher studies in preferred Western type institutions.…”
Section: Language Background In Lebanonmentioning
confidence: 99%